Are metabolic abnormalities the missing link between complete blood count-derived inflammatory markers and diabetic foot? Evidence from a large population study - Yang Zhang; Shumin Zhou; Xianbin Wang; Haiyan Zhou (PLoS ONE, 2025)
Background Diabetic foot is a serious complication of diabetes, and inflammation plays a key role in its pathogenesis. This population-based study investigates associations between complete blood count (CBC)-derived inflammatory markers and diabetic foot, while evaluating metabolic mediators in these relationships. Methods Data from 1,246 participants across three National Health and Nutrition Examination Survey (NHANES) cycles (1999–2004) were analyzed. Calculated inflammatory markers included monocyte-to-lymphocyte ratio (MLR), neutrophil-to-lymphocyte ratio (NLR), neutrophil-monocyte-to-lymphocyte ratio (NMLR), and systemic inflammatory response index (SIRI). Weighted logistic regression models assessed marker-diabetic foot associations, supplemented by subgroup and restricted cubic spline (RCS) analyses for nonlinearity. Mediation analysis quantified metabolic contributions. Results CBC-derived inflammatory markers demonstrated significant positive correlations with diabetic foot risk. Risk increased as quartiles for these markers increased. RCS analysis further revealed a significant nonlinear relationship between them. Serum creatinine (12.46%) and albumin (11.33%) mediated significant proportions of these associations. Conclusions CBC-derived inflammatory markers serve as accessible predictors of diabetic foot risk, with nonlinear patterns. The partial mediation by metabolic indicators highlights dual inflammatory-metabolic pathways in diabetic foot pathogenesis. Routine CBC-derived inflammatory markers monitoring could enable early risk stratification, while targeting metabolic abnormalities may amplify preventive strategies.